Das nicht klassische adrenogenitale Syndrom mit 21-Hydroxylase-Defekt bei Kindern und Jugendlichen - Dörr, Helmuth-Günther; Schulze, Nadja (Pädiatrische Praxis, 2020)
Non-classical AGS with 21-hydroxylase defect is a common monogenetic disorder that is often not diagnosed or diagnosed too late. The leading clinical symptom in girls is the premature pubarche before the 8th birthday. For diagnostic purposes, 17-OHP should be measured in serum in the morning for children in the first step and in the follicular phase for menstruating girls. The gold standard in diagnostics is the ACTH test, whereby cortisol should also be determined in the serum in addition to 17-OHP. The laboratory chemical diagnosis should in any case be confirmed by molecular genetic analysis. Drug therapy in children with hydrocortisone is carried out in a low dose if the clinical symptoms are progressive and, above all, there is a poor prognosis of the final size due to the acceleration of bone age. If a therapy with glucocorticoids is carried out, then an emergency ID card should also be issued.
CRIS-Team Scopus Importer:2021-04-19
Keywords: 17-OHP; ACTH test; Cortisol; CYP21A2; Premature pubarche